Method for Weed Management in organic farming - Saha, Sanjoy; Munda, Sushmita; Adak, Totan; Singh, Y V (Indian Farming, 2017)
Weeds can be effectively managed through better understanding of weed suppressing high yielding crop cultivars, pre-sowing seed bed tillage and appropriate seeding and weeding methods, judicious use of nutrients and irrigation water, proper crop rotations and use of bio-agents. The appropriate weed management approach can improve the crop productivity and profitability in organic farming.